PENDIDIK PENDIDIKAN ANAK USIA DINI (PAUD) SEBAGAI MODEL PERILAKU ANAK USIA DINI - Widya Ayu Puspita (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2010)
Early childhood educator is one on behavior model for children, especially in the early childhood education context, because of their intensive interaction with children. Behavior model can be verbal or nonverbal.Modelling process through four steps, these are acquisition, retention, performance and reinforcement. All of these steps flow through positive or negative reinforcement. For those reasonings, early childhood educator is expected to be a good model and strengthen children positive behavior. They have to keep their language, performance, attitude and practice.